comparison of the impacts of in-person and virtual conference attendance - Petra Dumbell; Gaby Haddow (Information Research: An International Electronic Journal)
Introduction. In-person conferences provide attendees with the opportunity to extend their knowledge, networks and sense of belonging in their field. This paper reports on an investigation that compared attendance at virtual and in-person conferences to identify differences in the impacts for delegates